2017
DOI: 10.1161/strokeaha.116.016225
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline Blood Pressure Effect on the Benefit and Safety of Intra-Arterial Treatment in MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment of Acute Ischemic Stroke in the Netherlands)

Abstract: Background and Purpose— High blood pressure (BP) is associated with poor outcome and the occurrence of symptomatic intracranial hemorrhage in acute ischemic stroke. Whether BP influences the benefit or safety of intra-arterial treatment (IAT) is not known. We aimed to assess the relation of BP with functional outcome, occurrence of symptomatic intracranial hemorrhage and effect of IAT. Methods— This is a post hoc analysis of the MR CLEAN (Multicenter Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 45 publications
4
78
0
3
Order By: Relevance
“…However, this threshold is based on the theoretical assumption that moderate arterial hypertension during acute ischemic stroke might be advantageous by improving cerebral perfusion of the ischemic penumbra in an unselected population of stroke patients without distinction between patients with and without successful reperfusion [2]. Two recent studies including patients from the MR CLEAN trial [6] and using a prospectively derived database of patients with IVT for large vessel occlusion strokes [7] showed a relationship between high admission SBP and poor functional outcome. These studies, however, do not answer the question on how blood pressure management should be performed after successful EVT.…”
Section: Introductionmentioning
confidence: 99%
“…However, this threshold is based on the theoretical assumption that moderate arterial hypertension during acute ischemic stroke might be advantageous by improving cerebral perfusion of the ischemic penumbra in an unselected population of stroke patients without distinction between patients with and without successful reperfusion [2]. Two recent studies including patients from the MR CLEAN trial [6] and using a prospectively derived database of patients with IVT for large vessel occlusion strokes [7] showed a relationship between high admission SBP and poor functional outcome. These studies, however, do not answer the question on how blood pressure management should be performed after successful EVT.…”
Section: Introductionmentioning
confidence: 99%
“…1 Goyal et al 22 have shown that higher admission SBP is an independent predictor of increased final infarct volume and a lower likelihood of favorable functional outcome in patients with large-vessel occlusion treated with EVT. However, given the overall poor evidence of BP management in patients with ischemic stroke and given the pathophysiological considerations mentioned above, active BP lowering in acute stroke patients with proximal vessel occlusion before recanalization might be harmful.…”
Section: Strokementioning
confidence: 99%
“…The post hoc analysis of data of the MR CLEAN trial (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) published in Stroke adds important new information about the risks and benefits of endovascular therapy (EVT) in acute stroke patients with different BP levels at baseline. Mulder et al 1 analyzed BP and the effect of EVT in the MR CLEAN study and showed that the effectiveness of EVT is similar in the entire range of baseline BP of the included patients. Furthermore, BP and EVT did not interact with the occurrence of symptomatic intracerebral hemorrhage (ICH) or other safety parameters.…”
Section: See Related Article P 1869mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence supports the impact of baseline systolic blood pressure (SBP) on mortality and functional outcome at 3 months in MT treated patients,2, 3 but data on the role of BP variability specifically during the procedure are sparse and limited. The definition of BP variability often differs across studies and the main hemodynamic parameters measured are SBP and mean arterial pressure 4.…”
Section: Introductionmentioning
confidence: 99%